Low-Power D-Band CMOS Amplifier for Ultrahigh-Speed Wireless Communications - Tuan Anh Vu; Kyoya Takano; Minoru Fujishima (Institute of Advanced Engineering and Science, 2018)
This paper presents a low-power D-Band amplifier suitable for ultrahigh-speed wireless communications. The three-stage fully differential amplifier with capacitive neutralization is fabricated in 40 nm CMOS provided by TSMC. Measurement results show that the D-band amplifier obtains a peak gain of 9.6 dB over a -3 dB bandwidth from 138 GHz to 164.5 GHz. It exhibits an output 1 dB compression point (OP1dB) of 1.5 dbm at the center frequency of 150 GHz. The amplifier consumes a low power of 27.3 mW from a 0.7 V supply voltage while its core occupies a chip area of 0.06 mm2.